Performance assessment of urine flow cytometry (UFC) to screen urines to reflex to culture in immunocompetent and immunosuppressed hosts. Issue 9 (September 2017) - Stefanovic, Aleksandra; Roscoe, Diane; Ranasinghe, Romali; Wong, Titus; Bryce, Elizabeth; Porter, Charlene; Lim, Adelina; Grant, Jennifer; Ng, Karen; Pudek, Morris
Abstract : Purpose. : Urine flow cytometry (UFC) is an automated method to quantify bacterial and white blood cell (WBC) counts. We aimed to determine whether a threshold for these parameters can be set to use UFC as a sensitive screen to predict which urine samples will subsequently grow in culture. Methodology. : Urines submitted to our microbiology laboratory at a tertiary care centre from 22 July 2015‐17 February 2016 underwent UFC (Sysmex UF‐1000i) analysis, regular urinalysis and urine culture. Positive urine cultures were defined as growth ≥10 4 c.f.u. ml −1 of organisms associated with urinary tract infections. The correlation of UFC bacterial and WBC counts with urine culture was assessed using receiver operating characteristics curves. The sensitivity (SN), specificity (SP), negative predictive values (NPVs), positive predictive values (PPVs) and false negative rate (FNR) were calculated at various thresholds in immunocompetent and immunosuppressed patients. Results. : A total of 15046 urine specimens were submitted, of which 14908 were analysable in the study. The average time to UFC result from receipt in the laboratory was 0.76 h (+/−1.04). The test performance at a set threshold of UFC bacteria ≥20 or WBC >5 was: SN=96.0%, SP=39.2%, PPV=47.0%, NPV=94.5% and FNR=4.0%. This threshold eliminates 26% of urine cultures. Immunosuppressed hosts had a lower sensitivity of 90.6% and a higher FNR of 9.4%. Conclusions. : UFC is a rapid and sensitive method to screen out urine samples that will subsequently be negative and to reflex urines to culture that will subsequently grow. UFC results are available within 1 h from receipt and enable the elimination of culture when the set threshold is not met.